Implementing Responsive Web Design to Improve Website Accessibility - Bayu Firmanto; Nanta Sigit (International Journal of Technology and Education Research, 2026)
The rapid growth of internet usage and the dominance of mobile device access have significantly transformed website development practices. Websites are no longer accessed primarily through desktop computers but through various devices with different screen sizes, particularly smartphones. This shift requires adaptive design strategies to ensure optimal accessibility and usability. However, many websites still employ static layouts that are not responsive, leading to display distortions, navigation difficulties, and reduced user experience, especially on mobile devices. This study aims to implement Responsive Web Design (RWD) to improve website accessibility and evaluate its effectiveness through quantitative measurement. The research adopts an experimental method using a before-and-after testing approach. The selected website is first evaluated in its original (non-responsive) condition using accessibility assessment tools based on Web Content Accessibility Guidelines (WCAG) standards. Subsequently, RWD principles—including fluid grids, flexible images, media queries, and a mobile-first approach—are implemented. Accessibility testing is then repeated to measure improvements. The results indicate that the implementation of Responsive Web Design significantly enhances website accessibility across multiple devices. Improvements are observed in layout adaptability, text readability, navigability, and overall compliance with WCAG principles. The responsive layout reduces horizontal scrolling, optimizes content structure, and enhances user interaction efficiency. In conclusion, Responsive Web Design is an effective technical solution for addressing accessibility challenges in multi-device environments. Although responsiveness alone does not guarantee full accessibility compliance, its integration with accessibility standards contributes substantially to improving digital service quality. This study provides empirical evidence and a structured implementation framework that can serve as a reference for developers and institutions seeking to enhance website accessibility and user experience.